Miconazole-loaded Nanostructured Lipid Carriers (NLC) for local delivery to the oral mucosa: improving antifungal activity - Mendes, A.I. (2020)
Miconazole is a widely used antifungal agent with poor aqueous solubility, which requires the development of drug delivery systems able to improve its therapeutic activity. For this purpose, a miconazole-loaded nanostructured lipid carriers (NLC) dispersion was prepared and characterized. Further, the dispersion was used to prepare a NLC-based hydrogel formulation proposed as an alternative system to improve the local delivery of miconazole to the oral mucosa. NLC dispersion showed particles in the nanometer range (≈200 nm) with low polidispersity index (<0.3), good physical stability and high encapsulation efficiency (>87%). A controlled miconazole release was observed from NLC and NLCbased hydrogel formulations, in contrast to a commercial oral gel formulation, which demonstrated a faster release. Additionally, it was observed that the encapsulation of miconazole in the NLC improved its antifungal activity against Candida albicans. Therefore, it was demonstrated that the encapsulation of miconazole in NLC allows for obtaining the same therapeutic effect of a commercial oral gel formulation, using a 17-fold lower dose of miconazole.